2010
DOI: 10.1002/mame.201000226
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Organosilane‐Modified Carbon Nanofibers and Influence of Silane Coating Thickness on the Performance of Polyethylene Nanocomposites

Abstract: Silane coatings with different thicknesses were synthesized on CNFs for reinforcement of polyethylene composites. The thickness of the silane coating was adjusted by using a basic catalyst to increase the overall reactivity of the silane groups, resulting in a thick coating of ≈46 nm (ca. 90% increase in fiber diameter). DMA performed on the polyethylene composites showed a substantial increase in storage modulus from 1.68 to 2.34 GPa (40%) at low temperatures in the composite with the thick silane coating (≈4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…These phenomena are more obvious in Comp-h ( Fig. 2E and F), revealing that heavy silane coating may induce an increased interaction and load transfer between filler and matrix [28]. Therefore, these results demonstrate that the silane coating enhanced interfacial interaction and adhesion in the HDPE/CNF system.…”
Section: Morphology and Wear Performance Of Nanocompositesmentioning
confidence: 74%
See 3 more Smart Citations
“…These phenomena are more obvious in Comp-h ( Fig. 2E and F), revealing that heavy silane coating may induce an increased interaction and load transfer between filler and matrix [28]. Therefore, these results demonstrate that the silane coating enhanced interfacial interaction and adhesion in the HDPE/CNF system.…”
Section: Morphology and Wear Performance Of Nanocompositesmentioning
confidence: 74%
“…The coating thicknesses were determined using TGA data, which are heavily silanized CNF-h (about 46 nm) and lightly silanized CNF-l (about 2.8 nm). Details of the treatment are provided in our previous study [28].…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the link between the silane-treated CNT and epoxy effectively change the movement of molecular chains reflected in Tan Delta. Other researches (Wood et al 2010) that involve DMA of Polymer Nanocomposites containing silanized CNFs with different silane treatments have found that silane reaction assisted by NaOH improve the interactions at interface level more than only silanization. Therefore, the storage modulus at -70 ºC of polymer nanocomposites reinforced with silanized CNFs increase 39 % with respect to polymer matrix (HDPE High Density Poly ethylene) .…”
Section: Dynamical Mechanical Analysismentioning
confidence: 98%